2021
DOI: 10.35631/ijepc.643022
|View full text |Cite
|
Sign up to set email alerts
|

The Experiences of Pre-Service Teachers Teaching Practicum During the Covid-19 Pandemic: A Systematic Literature Review

Abstract: The COVID-19 pandemic has resulted in the prohibition of close contact and this unprecedented issue has led to the abrupt closure of schools and universities across the country. Teacher education programs have taken a toll as the final year students would not be able to fully experience the working environment in a school during teaching practicum. Thus, this systematic literature review aims to explore the lived experiences of pre-service teachers teaching practicum experiences during the COVID-19 pandemic. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The findings of the current study bear some similarities to the relevant literature. To start with, it has been revealed that online platforms used during the pandemic period can offer unique learning and teaching experiences for pre-service English teachers as a kind of preparation for their future teaching career ( Brinia and Psoni, 2022 ; Kiok et al, 2021 ; Sepulveda-Escobar and Morrison, 2020 ). However, the participants mostly agreed that nothing could replace human interactions and preferred face-to-face education due to the opportunity of having hands-on interaction experiences and feeling real classroom dynamics ( Brinia and Psoni, 2022 ; Koşar, 2021 ; Sepulveda-Escobar and Morrison, 2020 ).…”
Section: Discussion Conclusion and Educational Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of the current study bear some similarities to the relevant literature. To start with, it has been revealed that online platforms used during the pandemic period can offer unique learning and teaching experiences for pre-service English teachers as a kind of preparation for their future teaching career ( Brinia and Psoni, 2022 ; Kiok et al, 2021 ; Sepulveda-Escobar and Morrison, 2020 ). However, the participants mostly agreed that nothing could replace human interactions and preferred face-to-face education due to the opportunity of having hands-on interaction experiences and feeling real classroom dynamics ( Brinia and Psoni, 2022 ; Koşar, 2021 ; Sepulveda-Escobar and Morrison, 2020 ).…”
Section: Discussion Conclusion and Educational Implicationsmentioning
confidence: 99%
“…The authors concluded that although the pre-service English teachers gained awareness about digital literacy and online learning platforms, they also encountered some difficulties due to poor Internet connection and lack of participation. Finally, a systematic analysis revealed that online teaching practicum experiences during the pandemic contributed to pre-service teachers’ attitudes, readiness level, and communication skills with stakeholders ( Kiok et al, 2021 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Thus, it is possible that Practicum students might have had limited opportunities to establish contact, communication and interaction with teaching staff in schools, to hold meetings with families to discuss follow-ups in tutorials or to establish links with students in schools [20][21][22][23]. On the other hand, students also appreciated positive aspects, in relation to the use of technology and the improvement of their digital competences [22,24,25], as well as regarding the possibilities offered by online learning in the educational process in any circumstance [21,23,26].…”
Section: Introductionmentioning
confidence: 99%